Profile of Brought in Dead Cases in a Tertiary Care Centre of South India (Indian Journal of Forensic Medicine & Toxicology, 2020)
Most of the times it is noticed that incidence of Brought in dead (BID) cases in a tertiary care hospital is veryhigh. But there are limited data of the statistics of such cases due to lack of records or audit. These casescan be due to natural cause or unnatural. The doctor attending such cases should be aware of all proceduresand formalities associated with BID cases. Diagnosis of death should be ascertained clinically and hospitalsshould be aware of the legal responsibilities of these cases.This study was conducted in a tertiary care institution where BID cases were profiled with the availabledata and records. The study throws light in to not only the demographic profile like age, sex, month wisedistribution but also to time of reporting to Emergency department (ED) as well as the probable cause basedon history of the informant. Males dominated in the total number of 307 cases compiled in 4 years, i.e, 2015to 2018. Age of above 60 years cases made the major share with sudden death as well as road traffic accident(RTA) being the major culprits. Maximum number of BID were reported during early morning hours (12amto 6 am) followed by late evening hours (6pm to 12am).